Handbook of research on supply chain management for sustainable development - Akkucuk, Ulas, 1975- (Business Science Reference, 2018)
"This book focuses on ethics and sustainability as it relates to managing a global supply chain. It also sheds light on ethical and sustainable supply chain management with respect to global supply chains by using cases, qualitative studies, literature reviews, empirical results and analysis of legal frameworks"- Resumé vydavatel
Keywords: logistika (management) -- environmentální aspekty; podnikový management -- environmentální aspekty; business logistics -- environmental aspects; industrial management -- environmental aspects; příručky; elektronické knihy; handbooks and manuals; electronic books